Erosão dentária em crianças diagnosticadas com a doença do refluxo gastroesofágico: estudo controlado - Patricia Alves Drummond de Oliveira (2015)
The purpose of this study was to investigate the impact of gastroesophageal reflux disease (GERD) on the experience of dental erosion (DE) in children and to analyse its association with diet, oral hygiene and sociodemographic characteristics. This crosssectionalcontrolled study encompassed 43 patients from Alfa Institute ofGastroenterology at the University Hospital of the Federal University of Minas Gerais. The children aged from 2 to 14 years-old were diagnosed positive for GERD by the 24- hour pH monitoring and paired by age group with 136 healthy controls from daycares and public schools, in the city of Belo Horizonte. DE was assessed by one calibrated examiner using the O'Sullivan index (inter-examiner Kappa: 0.90 and intra-examiner: 0.95). A questionnaire completed by parents collected information regardingsociodemographics, oral hygiene, dietary habits and medical history. Data analysis was performed by a multiple logistic regression according to Walds test (p< 0.05). Dental erosion was diagnosed in 10.6% (n=9) of the children; 25.6% (n=11) of the children with GERD and 5.9% (n=8) of the children without GERD, p=0.001) and it was not associated with dietary consumption, oral habits and socio-demographic characteristics. The multiple logistic regression final model showed that children diagnosed with GERD had a 7.01-fold [95% CI=2.2721.70; p=0.001] greater chance of presenting dental erosion than healthy children. In conclusion, children who were diagnosed positive with GERD were at an increased risk of having DE when compared to healthy subjects.